Establishment of triple-negative breast cancer cells based on BMI: A novel model in the correlation between obesity and breast cancer - Shveid Gerson, Daniela; Gerson‐Cwilich, Raquel; Lara Torres, Cesar Octavio; Chousleb de Kalach, Alberto; Ventura Gallegos, José Luis; Badillo‐Garcia, Luis Ernesto; Bargalló Rocha, Juan Enrique; Maffuz‐Aziz, Antonio; Sánchez Forgach, Ernesto Roberto; Castorena Roji, Gerardo; Robles Vidal, Carlos D.; Vargas‐Castillo, Ariana; et al. (Frontiers in Oncology, 2022)
Introduction Obesity has been associated with an increased risk of biologically aggressive variants in breast cancer. Women with obesity often have tumors diagnosed at later stages of the disease, associated with a poorer prognosis and a different response to treatment. Human cell lines have been derived from specific subtypes of breast cancer and have served to define the cell physiology of corresponding breast cancer subtypes. However, there are no current cell lines for breast cancer specifically derived from patients with different BMIs. The availability of those breast cancer cell lines should allow to describe and unravel functional alterations linked to these comorbidities. Methods Cell cultures were established from tumor explants. Once generated, the triple negative subtype in a patient with obesity and a patient with a normal BMI were chosen for comparison. For cellular characterization, the following assays were conducted: proliferation assays, chemo – sensitivity assays for doxorubicin and paclitaxel, wound healing motility assays, matrix invasion assays, breast cancer cell growth to estradiol by chronic exposure to leptin, induction of endothelial permeability and tumorigenic potential in athymic mice with normo - versus hypercaloric diets with an evaluation of the epithelium – mesenchymal transformation proteins. Results Two different cell lines, were established from patients with breast cancer: DSG-BC1, with a BMI of 21.9 kg/m2 and DSG-BC2, with a BMI of 31.5 kg/m2. In vitro, these two cell lines show differential growth rates, motility, chemosensitivity, vascular permeability, response to leptin with an activation of the JAK2/STAT3/AKT signaling pathway. In vivo, they displayed distinct tumorigenic potential. In particular, DSG-BC2, presented higher tumorigenicity when implanted in mice fed with a hypercaloric diet. Discussion To our knowledge, these primary cultures are the first in vitro representation of both breast cancer and obesity. DSG – BC2 presented a more aggressive in vivo and in vitro phenotype. These results support the hypothesis that breast cancer generated in an obese metabolic state may represent a contrasting variant within the same disease. This new model will allow both further comprehension, functional studies and the analysis of altered molecular mechanisms under the comorbidity of obesity and breast cancer.